Técnicas de classificação aplicadas a credit scoring: revisão sistemática e comparação - Frazzato Viana, Renato (Universidade Federal de São Carlos, 2015)
Nowadays the increasing amount of bank transactions and the increasing of data storage created a demand for risk evaluation associated with personal loans. It is very important for a company has a very good tools in credit risk evaluation because theses tools can avoid money losses. In this context, it is interesting estimate the default probability for a customers and, the credit scoring techniques are very useful for this task. This work presents a credit scoring literature review with and aim to give a overview covering many techniques employed in credit scoring and, a computational study is accomplished in order to compare some of the techniques seen in this text.
Classification techniques applied to credit scoring: a systematic review and comparison
Keywords: Credit-scoring; Data-mining; Risco de credito; Revisão; Técnicas; Credit-scoring; Data-mining; Review; Techniques; CIENCIAS EXATAS E DA TERRA::MATEMATICA